The rate with which spontaneous mutation alters the electrophoretic mobility of polypeptides. - Neel, J V (1986)
Studies of a Japanese population, involving a total of 539,170 locus tests distributed over 36 polypeptides, yielded three presumptive spontaneous mutations altering the electrophoretic mobility of the polypeptide. This corresponds to a mutation rate of 0.6 X 10(-5) per locus per generation. The a priori probability that undetected discrepancies between legal and biological parentage might in our test system result in an apparent electrophoretic mutation in this population is calculated to be only 0.3 X 10(-7) per locus per generation. Since electrophoresis only detects about half of the amino acid substitutions due to mutations of nucleotides, the corrected rate for mutations causing amino acid substitutions in polypeptides is 1.2 X 10(-5) per locus per generation. With allowance for synonymous mutations and those resulting in stop codons, the total mutation rate for nucleotide changes in the exons encoding a polypeptide becomes approximately equal to 1.8 X 10(-5) per locus per generation. When the present observations are combined with all of the other available data concerning mutation resulting in electrophoretic variants, the electrophoretic rate drops to 0.3 X 10(-5) per locus per generation, the total locus rate drops to roughly 1.0 X 10(-5), and the nucleotide rate drops to 1 X 10(-8). Even with this lower estimate, given approximately equal to 2 X 10(9) nucleotides in the haploid genome and an average of 10(3) exon nucleotides per polypeptide encoded, the implication, if these exon rates can be generalized, is of approximately equal to 20 nucleotide mutations per gamete per generation. This estimate of the frequency of "point" mutations does not include small duplications, rearrangements, or deletions resulting from unequal crossing-over, transcription errors, etc.